Analysis of the Cross Section Planning of Jepara’s Secondary Channels in Serayu Irrigation Area of Sumpiuh Irrigation Channels Cilacap Central Java - Prima Safitri Ayundaningtyas; Abdul Halim; Riman Riman (Widyagama University of Malang, 2022)
Central Java is one of the provinces in Indonesia that relies on the agricultural sector. The agricultural centre in the province is located in Cilacap regency. In order to improve agricultural products, adequate facilities and infrastructure are required, one of which is the Jepara Secondary Channel. Channels on the Secondary Channel Jepara majority is no longer worth using. So much agricultural land is less maximal in water utilization. On the Jepara secondary channel, there is no similar cross-section of channels; some use a cross-section of soil, stone, and concrete, and there is cross-sectional damage. In connection with the problem, a cross-sectional planning analysis of secondary channels needs to be conducted. Consider effective rainfall analysis, irrigation needs analysis, and open hydraulic analysis. The results obtained from the analysis should indicate that the discharge flowed by the existing channel (Qs) must be greater than or equal to the planned discharge (Q0). Based on the results, two channels cannot accommodate the discharge of water needs (Q0), namely in section 1 and section 6, so it needs to be redesigned. However, by analyzing cross sections along channels with a varied cross-section shapes. Then planned design for all fields by using alternative four. This is because using a cross-sectional combination of trapezoid and u-ditch 70x80 cm can shorten working time and make construction costs more affordable.